Pre-sarcopenia is associated with renal hyperfiltration independent of obesity or insulin resistance: Nationwide Surveys (KNHANES 2008–2011). Issue 26 (June 2017) - Han, Eugene; Lee, Yong-ho; Lee, Byung-Wan; Kang, Eun Seok; Cha, Bong-Soo
Abstract : Abstract: Renal hyperfiltration is closely linked to cardiometabolic disorders, and it may increase the mortality risk of the general population. Despite the well-established association between cardiometabolic diseases and sarcopenia, the relationship between renal hyperfiltration and sarcopenia has not yet been assessed. This population-based, cross-sectional study used a nationally representative sample of 13, 800 adults from the 2008 to 2011 Korea National Health and Nutrition Examination Survey. Renal hyperfiltration was defined as the age- and sex-specific glomerular filtration rate above the 90th percentile in subjects with normal kidney function (>60 mL/min/1.73 m 2 ). Appendicular skeletal muscle (ASM), measured by dual-energy x-ray absorptiometry, was used to assess pre-sarcopenia, which the international consensus defines as both ASM per se and ASM that was adjusted for the body mass index and the height. A total of 1402 (10.2%) participants were classified as having renal hyperfiltration. The prevalence of pre-sarcopenia ranged from 11.6% to 33.0%, by definition. Individuals with pre-sarcopenia had higher risks of renal hyperfiltration compared to those without pre-sarcopenia (10.9% vs 17.4%, P  < .001; odds ratio [OR] = 1.71, 95% confidential interval [CI] = 1.48–1.99, P  < .001). Multiple logistic regression analyses also demonstrated this independent association between pre-sarcopenia and renal hyperfiltration, following adjustment for confounding factors such as insulin resistance and obesity (OR = 1.84, 95% CI = 1.57–2.15, P  < .001). In the general population of healthy individuals, pre-sarcopenia might be associated with renal hyperfiltration independent of obesity or insulin resistance.